EVALUASI KINERJA KEUANGAN PEMERINTAH DALAM â€œPROGRAM DUKUNGAN MANAJEMEN DAN TUGAS TEKNIS LAINNYA KEMENTERIAN AGAMAâ€ DENGAN MENGGUNAKAN METODE VALUE FOR MONEY PADA KANTOR KEMENTERIAN AGAMA PROVINSI SULAWESI UTARA - Nainu, Rismawaty; Sondakh, Jullie J.; Budiarso, Novi S. (Universitas Sam Ratulangi, 2017)
Value for money in the context of regional autonomy is a bridge to deliver local governments to achieve good governance. To support the implementation of public funds management (public money), which based on the concept of value for money, it is necessary to have good regional financial management system and local budget. The purpose of this study is to know how the government's performance in management support programs and other technical task implementers if using the method of value for money. The method used in this research is qualitative descriptive method that quantitative. The results showed that the calculation of economic ratios showed less than 90% which means quite economical in the standard value for money. Thus the Office of the Ministry of Religious Affairs of North Sulawesi Province is economical in the expenditure of its spending budget. The efficiency ratio shows less than 100% result which means quite efficient in standard value for money. Thus the Office of the Ministry of Religious Affairs of North Sulawesi Province quite efficient in the expenditure of spending budget. The effectiveness ratio shows the result is above 100% (> 100%) so it shows the Ministry of Religious Affairs Office of North Sulawesi Province is very effective in expenditure budget utilization. Keywords: Financial Performance,Â Value for Money Method